A presença feminina nos espaços legislativos: um estudo das eleições de 2010 para a Assembleia Legislativa de Minas Gerais - Larissa Peixoto Vale Gomes (2012)
The participation of women in institutional politics is still small in the world and in Brazil. The exclusion of women from positions of power comes from a structural inequality with strong historical roots which come in play when a woman attempts to be a candidate for political office and finds great difficulties to accomplish that. Brazilian culture, combined with a fragmented political system that encourages individualized campaigns that are very expensive, weigh excessively on women. Besides gender bias, Brazilian women have only come in to politics recently and suffer with the lack of experience and connections in the political world. The study looks to understand from the candidates to the position of state assemblywoman of Minas Gerais what the main obstacles in the 2010 campaign were. Along with that information, gathered through a survey, semi-structured interviews with state party president look to understand the positions of the parties as it relates to female candidatures.